Aspectos ambientais e socioeconômicos da carcinicultura no estado do Ceará, Brasil: a visão dos empregados e moradores da comunidade de entorno - Almeida, Sérgio Alberto Apolinário (2014)
The cultivation of shrimp, or shrimp farming, has become one of the main sectors of the world fish production industry in terms of expansion and market value. In Brazil, marine shrimp cultivation covers an area of approximately 18,500 ha and 6,580 of them are located in the State of Ceará that had an estimated production of 35,000 tons in the year 2012. In comparison with other countries, Brazilian shrimp farming had a moderate development occupying an area of cultivationless than 20,000 ha.However, despite the importance of shrimp farming in developmentof the rural economy, a lot of criticism has been made without the appropriate technical and/or scientific evidence about possible environmental and social impacts of the industry.The main objective of this research was to analyze the potential environmental and socioeconomic impacts of marine shrimp farms in the estuaries of the rivers Jaguaribe (Municipality of Aracati), Acaraú (Municipality of Acaraú) and Coreaú (Municipalities of Camocim and Granja), in the view of employees and residents of neighboring communities.Data collection took place in the period of July 2013 to January 2014 and it were used questionnaires and interviews with the employees and residents of the neighboring communities of the areas adjacent to shrimp farms. The data produced after the questionnaires were coded and stored in EXCEL software and processed according CONOVER (1999).Aspects concerning to the employees in the farms had indicateda Quality of Life Index (QLI) of 0.70, indicating a “medium” level of quality of life. Similarly, aspects inherent to the impacts caused by the shrimp farms to the residents, showing Quality of Life Index (QLI) of 0.77, indicating a “medium”level of quality of life. Finally, the calculation on the Environmental Quality Index (EQI) and the Environmental Sustainability Index (ESI) of the shrimp farms indicated values of 0.81 and 0.88, respectively. As suggestion for future studies, it would be interesting to identify, economically and technologically, viable optionsto to solve or mitigate the negative environmental impactsrelated to a future expansion of shrimp farms in the region.